High-temperature-resistant flexible transducer and preparation method and application thereof
By using a PI-CNTs composite film with a micro-nano double-stage structure on the surface and a copper electrode interlocking structure combined with a silicone-based high-temperature fireproof material packaging layer, the structural failure problem of existing high-temperature ultrasonic transducers in high-temperature environments is solved, and efficient ultrasonic conversion and good high-temperature flexibility are achieved.
Patent Information
- Application Number
- CN202311432754.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-31
- Publication Date
- 2025-05-02
AI Technical Summary
The existing high-temperature resistant ultrasonic transducers have structural failure problems such as material degeneration, internal cracks and corrosion in high-temperature environments, and have low conversion efficiency, poor flexibility and narrow temperature resistance range.
A high-temperature-resistant flexible transducer is formed by interlocking the PI-CNTs composite film with a micro-nano double-stage structure on the surface and a copper electrode attached to the surface of the PI-CNTs composite film, and a package layer is prepared by a silicone-based high-temperature fireproof material.
It improves the thermal and dielectric properties of the transducer, enhances the response ability to high-frequency weak vibrations, improves ultrasonic reception and emission performance, and has good high temperature resistance.
Smart Images

Figure CN119909918A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of flexible transducer preparation, and in particular relates to a high temperature resistant flexible transducer and a preparation method and application thereof. Background Art
[0002] Industrial equipment in high-temperature environments is prone to structural failures such as material degradation, internal cracks, and corrosion, which can lead to economic losses and safety accidents. When conventional ultrasonic transducers are used to detect high-temperature industrial equipment, it is usually necessary to add delay blocks to isolate the high-temperature surface. However, this method has many limitations, such as short continuous working time, severe sound wave attenuation, and inapplicability to irregular structure surfaces. In recent years, researchers have tried to develop high-temperature resistant ultrasonic transducers through piezoelectric, electromagnetic and other sensing principles. However, ultrasonic transducers prepared based on the above sensing principles still have some problems in practical applications, such as low conversion efficiency, poor flexibility and narrow temperature resistance range.
[0003] To improve this problem, ultrasonic transducers based on triboelectric generators (TENGs) have been valued by the sensor research community. However, due to the limitations of material selection and structural design, it is difficult for existing TENG-based ultrasonic transducers to have both flexibility and high-frequency response capabilities. At the same time, in order to obtain higher output performance, researchers usually choose polymers with high electronegativity as friction layer materials. However, it is difficult for polymer materials to maintain good mechanical stability in high-temperature environments, which means that the temperature resistance of the transducer needs to be further improved. Summary of the invention
[0004] In view of the above problems, the present invention provides a high temperature resistant flexible transducer and its preparation method and application, wherein the high temperature resistant flexible sensor is formed by interlocking a PI-CNTs composite film having a micro-nano dual-stage structure on the surface and a copper electrode attached to the surface of the PI-CNTs composite film, wherein the encapsulation layer is prepared from a silicone-based high temperature fireproof material. Among them, the introduction of CNTs nanoparticles can not only effectively improve the thermal properties and dielectric properties of the PI (polyimide) film, but also promote the formation of a micro-nano dual-stage convex structure on the surface of the PI film. Moreover, due to the good mechanical transmission between the interlocking structures, the introduction of the micro-nano dual-stage interlocking structure can improve the response ability of the transducer to high-frequency weak vibrations. Similarly, the discharge of air inside the transducer can increase the deformation displacement of the interlocking structure under the action of external force, further improving the ultrasonic receiving performance of the transducer. In addition, the reduction of the gap distance between the two electrodes enhances the electrostatic force, thereby improving the ultrasonic emission performance of the transducer.
[0005] The first object of the present invention is to provide a high temperature resistant flexible transducer, the flexible transducer comprising a PI-CNTs superimposed thin film layer and a packaging layer bonded to the upper and lower surfaces of the PI-CNTs superimposed thin film layer;
[0006] The PI-CNTs stacked film layer is formed by interlocking a positive electrode PI-CNTs composite film and a negative electrode PI-CNTs composite film. The positive electrode PI-CNTs composite film and the negative electrode PI-CNTs composite film are both composed of a PI-CNTs composite film with a micro-nano dual-level structure and a copper layer attached to the surface of the PI-CNTs composite film. PI is the abbreviation of polyimide, and CNTs is the abbreviation of carbon nanotubes.
[0007] In an embodiment of the present invention, the encapsulation layer is composed of a single-sided adhesive film made of a silicone-based high-temperature fireproof material.
[0008] In the embodiment of the present invention, the specific preparation process of the single-sided adhesive film is as follows:
[0009] The silicone-based colloid is dropped onto a glass substrate and coated into a film using a coater;
[0010] Curing at room temperature for 2-3 hours to obtain a single-layer sealing film;
[0011] The high-temperature sealing colloid is dropped again on the surface of the solidified single-layer high-temperature sealing film, and is spread evenly using a coater to obtain a single-sided adhesive film.
[0012] In the embodiment of the present invention, the thickness of the single-sided adhesive film is 40-50 μm.
[0013] In the embodiment of the present invention, the thickness of the PI-CNTs composite film is 50-70 μm.
[0014] In the embodiment of the present invention, the copper layer has a thickness of 300-350 nm.
[0015] In an embodiment of the present invention, the PI-CNTs stacked thin film layer is prepared by the following steps:
[0016] The evenly dispersed PI-CNTs mixed solution is evenly spin-coated on the semicircular pit template, and then heated and cured, and peeled off to obtain a PI-CNTs composite film with a micro-nano dual-level structure on the surface;
[0017] Depositing copper on the front side of a PI-CNTs composite film and the back side of another PI-CNTs composite film respectively to obtain a positive electrode PI-CNTs composite film and a negative electrode PI-CNTs composite film;
[0018] The positive electrode PI-CNTs composite film and the negative electrode PI-CNTs composite film are stacked in a manner that the film surfaces with copper attached are facing back to back to obtain a PI-CNTs stacked film layer.
[0019] In the embodiment of the present invention, the PI-CNTs mixed solution is made of CNTs nano powder and PI solution, and the CNTs nano powder accounts for 0-1.5% of the mass of the PI-CNTs composite film, excluding zero.
[0020] In the embodiment of the present invention, the spin coating speed is 800-900 r / s.
[0021] In an embodiment of the present invention, the heating curing conditions are: heating rate of 60-70°C / h, keeping warm at 80-90°C for 1-1.5 hours, keeping warm at 140-145°C for 1-2 hours, and keeping warm at 260-270°C for 1-2 hours.
[0022] In an embodiment of the present invention, the deposition method is magnetron sputtering.
[0023] The second object of the present invention is to provide a method for preparing a high temperature resistant flexible transducer, comprising:
[0024] The evenly dispersed PI-CNTs mixed solution is evenly spin-coated on the semicircular pit template, and then heated and cured, and peeled off to obtain a PI-CNTs composite film with a micro-nano dual-level structure on the surface;
[0025] Depositing copper on the front side of a PI-CNTs composite film and the back side of another PI-CNTs composite film respectively to obtain a positive electrode PI-CNTs composite film and a negative electrode PI-CNTs composite film;
[0026] The positive electrode PI-CNTs composite film and the negative electrode PI-CNTs composite film are stacked in a manner that the film surfaces with copper attached are facing each other, thereby obtaining a PI-CNTs stacked film layer;
[0027] A single-sided adhesive film is stacked on the upper and lower surfaces of the PI-CNTs stacked film layer, and a stainless steel roller is used to roll the PI-CNTs stacked film layer from one side to the other side to form a packaging layer, thereby obtaining a flexible transducer.
[0028] The third object of the present invention is to provide an application of a high temperature resistant flexible transducer, and the application of the high temperature resistant flexible transducer as described above in thickness measurement at 0-200°C and quantitative detection of pipeline defects.
[0029] Beneficial effects of the present invention:
[0030] The high temperature resistant flexible transducer provided by the present invention is based on the coupling effect of friction electrification and electrostatic force effect. The micro-nano interlocking structure has good mechanical transmission between the structures. The introduction of the micro-nano interlocking structure can improve the response ability of the transducer to high-frequency weak vibrations. Similarly, the discharge of air inside the high temperature resistant flexible transducer can increase the deformation displacement of the interlocking structure under the action of external force, further improving the ultrasonic receiving performance of the transducer. In addition, the reduction of the gap distance between the two electrodes enhances the electrostatic force, thereby improving the ultrasonic emission performance of the transducer.
[0031] Compared with a smooth planar structure, the micro-nano two-stage interlocking structure can effectively increase the contact area between the friction layers and increase the deformation displacement of the transducer under external pressure, thereby improving the transducer's response to weak high-frequency vibrations.
[0032] Furthermore, the air inside the high temperature resistant flexible transducer is completely removed to increase the deformation displacement of the interlocking structure under the action of external force and reduce the distance between electrodes, thereby improving the ultrasonic receiving and transmitting performance of the transducer;
[0033] The micro-nano interlocking structure is jointly created by the addition of CNTs nanoparticle raw materials and the preparation method of thermal curing of the semicircular pit template, wherein the introduction of CNTs nanoparticles also improves the thermal properties and dielectric properties of the PI film, thereby providing the temperature resistance and dielectric properties of the obtained flexible transducer;
[0034] In summary, the high temperature resistant flexible transducer obtained by the present invention has good ultrasonic transmitting and receiving performances, and has the characteristics of flexibility and high temperature resistance.
[0035] Other features and advantages of the present invention will be described in the following description, and partly become apparent from the description, or understood by practicing the present invention. The purpose and other advantages of the present invention can be realized and obtained by the structures pointed out in the description, claims and drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0037] Figure 1 A schematic structural diagram of a high temperature resistant flexible transducer according to an embodiment of the present invention is shown;
[0038] Figure 2 A flow chart showing a method for preparing a high temperature resistant flexible transducer according to an embodiment of the present invention is shown;
[0039] Figure 3 A flow chart showing the preparation of a PI-CNTs composite film having a micro-nano dual-level structure according to an embodiment of the present invention;
[0040] Figure 4 A flow chart of preparing a single-sided adhesive film according to an embodiment of the present invention is shown;
[0041] Figure 5 A packaging flow chart of a flexible transducer according to an embodiment of the present invention is shown;
[0042] Figure 6 The SEM image of the surface microstructure of the undoped PI film and the PI-CNTs composite film with a CNTs content of 1% according to an embodiment of the present invention is shown;
[0043] Figure 7 A parallel or perpendicular conduction diagram of the heat flow path of the PI-CNTs composite material according to an embodiment of the present invention is shown;
[0044] Figure 8 The thermogravimetric curves of the PI-CNTs composite film at different CNTs contents according to an embodiment of the present invention are shown;
[0045] Fig. 9 A schematic diagram of a dielectric model of a PI-CNTs composite film according to an embodiment of the present invention is shown;
[0046] Fig.10 A dielectric constant measurement curve of a PI-CNTs composite film at different CNTs contents according to an embodiment of the present invention is shown;
[0047] Fig.11 A working principle diagram of an electromechanical transducer device based on triboelectric effect according to an embodiment of the present invention is shown;
[0048] Fig.12 A schematic diagram showing the force on a rectangular surface element of a PI film according to an embodiment of the present invention is shown;
[0049] Fig.13 A diagram showing the coupling simulation results of the high temperature resistant flexible transducer in the transmitting mode and the receiving mode according to an embodiment of the present invention;
[0050] Fig.14 The steady-state potential distribution diagram of the high temperature resistant flexible transducer under different initial voltages according to an embodiment of the present invention is shown;
[0051] Fig.15 A diagram showing the deformation state of a high temperature resistant flexible transducer under the action of electric fields of different frequencies according to an embodiment of the present invention;
[0052] Fig.16A diagram showing different deformation states of a high temperature resistant flexible transducer under the action of ultrasonic sound fields of different frequencies according to an embodiment of the present invention;
[0053] Fig.17 The friction charge transfer principle analysis diagram according to an embodiment of the present invention is shown;
[0054] Fig.18 A simulation analysis diagram showing the response capability of different structures to weak pressure according to an embodiment of the present invention is shown;
[0055] Fig.19 A diagram showing the laser test result of a high temperature resistant flexible transducer according to an embodiment of the present invention;
[0056] Fig. 20 A diagram showing the high temperature performance test results of high temperature resistant flexible transducers with different CNTs contents according to an embodiment of the present invention;
[0057] Fig.21 A diagram showing the comparative test results of FHTUT and ultrasonic thickness gauge according to an embodiment of the present invention;
[0058] Fig. 22 A diagram showing quantitative detection of high temperature pipeline defects according to an embodiment of the present invention is shown;
[0059] Fig.23 A scene diagram of a quantitative detection test of high-temperature pipeline defects according to an embodiment of the present invention is shown;
[0060] Fig.24 A diagram showing the quantitative detection result of high temperature pipeline defects according to an embodiment of the present invention is shown;
[0061] In the figure:
[0062] 10. PI-CNTs superimposed film layer; 11. PI-CNTs composite film; 12. Copper layer; 20. Encapsulation layer. DETAILED DESCRIPTION
[0063] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0064] like Figure 1 As shown, a high temperature resistant flexible transducer according to an embodiment of the present invention, Figure 1 In the figure, a is a schematic diagram of the structure of a high temperature resistant flexible transducer, and b is an enlarged schematic diagram of the dotted frame portion in a;
[0065] The high temperature resistant flexible transducer comprises a PI-CNTs superimposed thin film layer 10 and a packaging layer 20 bonded to the upper and lower surfaces of the PI-CNTs superimposed thin film layer 10;
[0066] The PI-CNTs stacked film layer 10 is formed by interlocking a positive electrode PI-CNTs composite film and a negative electrode PI-CNTs composite film, and the positive electrode PI-CNTs composite film and the negative electrode PI-CNTs composite film are both composed of a PI-CNTs composite film 11 with a micro-nano dual-level structure and a copper layer 12 attached to the surface of the PI-CNTs composite film.
[0067] In the embodiment of the present invention, the thickness of the PI-CNTs composite film 11 is 50-70 μm.
[0068] In the embodiment of the present invention, the thickness of the copper layer 12 is 300-350 nm.
[0069] In the embodiment of the present invention, the encapsulation layer 20 is formed by a single-sided adhesive film made of a silicone-based high-temperature fireproof material, wherein the thickness of the single-sided adhesive film is 40-50 μm.
[0070] like Figure 2 As shown, a method for preparing a high temperature resistant flexible transducer according to an embodiment of the present invention includes:
[0071] Step 1: Spin-coat the evenly dispersed PI-CNTs mixture onto the semicircular pit template, heat and cure it, and peel it off to obtain a PI-CNTs composite film 11 with a micro-nano dual-level structure on the surface;
[0072] Step 2: depositing copper on the front side of the PI-CNTs composite film 11 and the back side of another PI-CNTs composite film 11 to obtain a positive electrode PI-CNTs composite film and a negative electrode PI-CNTs composite film;
[0073] Step 3, the positive electrode PI-CNTs composite film and the negative electrode PI-CNTs composite film are stacked in a manner that the film surfaces with copper attached are facing each other, to obtain a PI-CNTs stacked film layer 10;
[0074] Step 4: stack a single-sided adhesive film on the upper and lower surfaces of the PI-CNTs stacked film layer 10, and use a stainless steel roller to roll the PI-CNTs stacked film layer 10 from one side to the other side to remove the internal air to form a packaging layer 20 to obtain a flexible transducer.
[0075] In step 1, the PI-CNTs mixed solution is made of CNTs nanopowder and PI solution, wherein the CNTs nanopowder accounts for 0-1.5% (excluding zero) of the mass of the PI-CNTs composite film;
[0076] In step one, the spin coating speed is 800-900r / s, and the specific value of the spin coating speed is any one of 800r / s, 810r / s, 820r / s, 830r / s, 840r / s, 850r / s, 860r / s, 870r / s, 880r / s, 890r / s, and 900r / s.
[0077] In step 1, the heating curing conditions are: heating rate of 60-70°C / h, keeping warm at 80-90°C for 1-1.5 hours, keeping warm at 140-145°C for 1-2 hours, and keeping warm at 260-270°C for 1-2 hours;
[0078] Specifically, the specific value of the heating rate is any one of 61°C / h, 62°C / h, 63°C / h, 64°C / h, 65°C / h, 66°C / h, 67°C / h, 68°C / h, 69°C / h, and 70°C / h;
[0079] During the curing process, the temperature is kept at 80-90°C for 1-1.5 hours, and the specific temperature value is any one of 81°C, 82°C, 83°C, 84°C / h, 85°C, 86°C, 87°C, 88°C, 89°C / h, and 90°C; the specific holding time value is any one of 1 hour, 1.2 hours, 1.3 hours, and 1.5 hours;
[0080] During the curing process, the temperature is kept at 140-145°C for 1-2 hours, and the specific temperature value is any one of 141°C, 142°C, 143°C, 144°C / h, and 145°C; the specific holding time value is any one of 1 hour, 1.2 hours, 1.3 hours, 1.5 hours, 1.6 hours, 1.8 hours, and 2 hours;
[0081] During the curing process, the temperature is kept at 260-270°C for 1-2 hours. The specific temperature value is any one of 261°C, 262°C, 263°C, 264°C / h, 265°C, 266°C, 267°C, 268°C, 269°C / h, and 270°C; the specific holding time is any one of 1 hour, 1.2 hours, 1.3 hours, 1.5 hours, 1.6 hours, 1.8 hours, and 2 hours.
[0082] In certain specific embodiments of the present invention, the flow chart of preparing the PI-CNTs composite film 11 having a micro-nano dual-level structure in step 1 is as follows: Figure 3 As shown, it includes the preparation of a uniformly dispersed PI-CNTs mixed solution, the preparation of a semicircular pit template and the preparation of a film by thermal curing; Figure 3In the figure, spherical knife refers to a spherical knife; notches refers to circular cuts; template refers to a template (i.e., a semicircular pit template in the embodiment of the present invention); heat curing refers to heat curing; stripping refers to stripping;
[0083] The preparation of the uniformly dispersed PI-CNTs mixed solution is specifically as follows:
[0084] CNTs (carbon nanotubes) nanopowder is added to the PI solution to obtain a PI-CNTs mixed solution; then, the mixed solution is placed on a magnetic stirrer and stirred for 10-20 minutes to allow the CNTs to be initially dispersed in the PI solution; finally, it is subjected to ultrasonic treatment for 1-1.5 hours to obtain a uniformly dispersed PI-CNTs mixed solution.
[0085] The preparation of the semicircular pit template is as follows:
[0086] A micron-scale semicircular pit structure was machined on the surface of a stainless steel block using a high-speed micro-spherical tool, and was used as a template for microstructure processing.
[0087] In step 2, the copper deposition is deposited on the surface of the PI-CNTs composite film 11 by magnetron sputtering.
[0088] In certain embodiments of the present invention, in step 3, the specific preparation process of the single-sided adhesive film is as follows:
[0089] The silicone-based colloid is dropped onto a glass substrate and coated into a film using a coater;
[0090] Curing at room temperature for 2-3 hours to obtain a single-layer sealing film, wherein the thickness of the single-layer sealing film is 40-50 μm;
[0091] The high-temperature sealing colloid is dropped again on the surface of the solidified single-layer high-temperature sealing film, and spread evenly using a coater to obtain a single-sided adhesive film. It can be seen that the obtained single-sided adhesive film is made of silicone-based colloid (a high-temperature resistant and fire-proof material) and has good high-temperature resistance.
[0092] The preparation process of the above-mentioned single-sided adhesive film is as follows Figure 4 As shown, Figure 4 Herein, Applicator is an applicator; Sealant is a sealant (i.e., a silicone-based colloid in the embodiment of the present invention); Coating is coating; Curing is curing; Single layer film is a single-layer sealing film; and Single-side tape is a single-sided tape.
[0093] Step 2, step 3 and step 4 combined can also be called the packaging of the flexible transducer. The packaging process diagram is as follows: Figure 5 As shown, Figure 5 In the figure, Magnetron sputtering is magnetron sputtering, Bottom electrode is bottom electrode (corresponding to one of the positive electrode PI-CNTs composite film and the negative electrode PI-CNTs composite film in the present invention), Top electrode is top electrode (one of the positive electrode PI-CNTs composite film and the negative electrode PI-CNTs composite film), Rolling encapsulation is rolling encapsulation, FHTUT is the abbreviation of Flexible High-temperature Triboelectric Ultrasonic Transducer, which corresponds to the high temperature resistant flexible transducer in the present invention.
[0094] Example
[0095] According to step 1 in the above embodiment, PI-CNTs composite films with different CNTs contents were prepared, and then the performance was characterized;
[0096] Then, the PI-CNTs composite films with different CNTs contents were used to prepare high-temperature resistant flexible transducers with different CNTs contents according to step 2, step 3 and step 4 in the above embodiment, and the performance of the high-temperature resistant flexible transducers was characterized.
[0097] 1. Preparation and performance characterization of PI-CNTs composite films with different CNTs contents
[0098] According to step 1 in the above embodiment, PI-CNTs composite films with different CNTs contents were prepared, and then the performance was characterized.
[0099] Doping CNTs in PI film can not only introduce nanostructures on the film surface, but also has an important influence on the thermal and electrical properties of PI film. First, the surface morphology of PI-CNTs composite film was characterized by scanning electron microscopy. Then, based on the theory of heat conduction, the thermal conductivity model of PI-CNTs composite film was established, and its thermal stability was tested and analyzed. Finally, based on the dielectric theory, the dielectric model of PI-CNTs composite film was established, and its dielectric constant was tested and analyzed.
[0100] The surface morphology of undoped PI film and PI-CNTs composite film was characterized by field scanning electron microscopy (TESCAN MIRA3). Figure 6 The SEM images of the surface microstructure of the undoped PI film and the PI-CNTs composite film with a CNTs content of 1% are shown. Figure 6In the figure, row a shows PI-CNTs composite films with a CNTs content of 1%, row b shows the surface microscopic morphology of PI films without CNTs doping, the second and third pictures from left to right in row a are enlarged pictures of the dotted box part in the previous picture, and the second and third pictures from left to right in row b are enlarged pictures of the dotted box part in the previous picture;
[0101] from Figure 6 It can be seen that the surface of the PI film without CNTs doping is uniformly distributed with micron-protrusion structures, with a diameter of about 150μm, but the surface of the micron-protrusion structure is relatively smooth, without nano-protrusion structures; and the surface of the PI-CNTs composite film with a CNTs content of 1% is also uniformly distributed with micron-protrusion structures, with a diameter of about 150μm, but unlike the PI film without CNTs doping, the nano-protrusion structure caused by CNTs can be clearly observed on the surface of the micron-protrusion structure;
[0102] CNTs, as thermally conductive particles, are dispersed in the PI matrix to form a thermal conduction path, which increases the thermal conductivity of the composite film and further enhances the thermal stability of the polymer material. In order to analyze the thermal conductivity of composite materials, researchers have adopted several different theoretical analysis methods based on Fourier's law to define thermal conductivity to establish various types of thermal conductivity models, mainly including uniform models, effective medium models, heterogeneous models and random dispersion models. However, there are many factors that affect the thermal properties of composite materials, such as dispersion degree, interfacial thermal resistance, etc., which leads to the problems of narrow application range and slow calculation speed of the above models. The mixed regular thermal conductivity model is a method to calculate the overall thermal conductivity based on the weighted average of the thermal conductivities of each component in the composite material. It has the advantages of wide applicability, high efficiency and speed. For the mixed regular thermal conductivity model, the thermal conductivity of the composite material can be predicted based on the difference in the parallel or perpendicular relationship between the heat flow path conduction direction in the two phases and the scale direction of the thermally conductive filling particles, such as Figure 7 As shown, Figure 7 In the figure, Heat flow refers to the heat sink and Heat flowpath refers to the hot runner.
[0103] The expressions of the series-parallel model of PI-CNTs composite film materials are shown in formula (1) and formula (2):
[0104]
[0105]
[0106] Wherein, subscripts m and c represent polymer and CNTs, respectively; k eff|| is the effective thermal conductivity of the PI-CNTs composite system in the series model; k eff⊥is the effective thermal conductivity of the composite material system in the parallel model; k c and k m represent the thermal conductivity of CNTs and PI matrix materials, respectively; and Represent the volume coefficients of CNTs and PI matrix materials, respectively. The above analysis shows that there is a positive correlation between thermal conductivity and volume fraction, and the thermal conductivity of CNTs itself is much higher than that of PI material. Therefore, the introduction of CNTs effectively improves the thermal conductivity of PI matrix.
[0107] Thermogravimetric curve is an experimental data curve in thermal analysis technology, which is used to reflect the mass change of the sample under test as the temperature changes. To verify the above theory, the thermogravimetric curve of the PI-CNTs composite film was tested using a thermogravimetric analyzer (NETZSCH TG 209F1 Libra). The test results Figure 8 shown. Figure 8 Thermogravimetric analysis curves of PI-CNTs composite films with different CNTs contents. Figure 8 It can be seen that the thermal decomposition temperature of the non-CNTs doped PI film is 550°C; while the PI-CNTs composite film still maintains good stability at 550°C, and it does not begin to gradually decompose until the temperature is higher than 560°C, so its stability is higher than that of the non-CNTs doped PI film. In addition, when the temperature is 800°C, the residual mass of the PI-CNTs composite film (59.1%) is significantly higher than that of the non-CNTs doped PI film (58%). The test results show that the addition of a certain amount of CNTs improves the thermal stability of the film material.
[0108] CNTs are dispersed in the PI matrix as conductive fillers, which increases the dielectric constant of the composite film. In order to analyze the dielectric properties of composite materials, researchers have established a variety of dielectric models according to different doping conditions, including the Lichtenecker model, the Maxwell-Garnett model and the Bruggeman model. However, due to the large number of influencing factors of composite materials, such as the degree of dispersion and various shapes, the above models have limitations such as a narrow range of use and large calculation errors. The series-parallel hybrid model describes the electrical properties of the entire material by decomposing the material into multiple subsystems and connecting them together in parallel or series to form a complete system. It has the characteristics of strong flexibility and high scalability. Since the dielectric constants of the two materials that make up the composite system are often not similar, Newnhanm et al. proposed two basic ideal models for the microscopic mechanism of this two-component composite material, such as Fig. 9 shown. Fig. 9 In the figure, a is a schematic diagram of the series model; b is a schematic diagram of the parallel model; c is a schematic diagram of the series-parallel model.
[0109] For the series model, it is assumed that the composite material consists of fillers and matrix, and the fillers and matrix are arranged in sequence. Under the action of the electric field, the dielectric polarization of each component will affect each other, thereby affecting the overall dielectric properties of the composite material. Considering the influence of the volume fraction of each component on the dielectric properties, the dielectric constant of the composite material can be obtained as:
[0110] 1 / ε=v 1 / ε 1 +v 2 / ε 2 (3)
[0111] For the parallel model, it is assumed that the composite material consists of filler and matrix, and the filler and matrix are a uniformly mixed structure. Under the action of the electric field, the dielectric polarization of each component is independent of each other, so the overall dielectric constant of the composite material can be regarded as the weighted average of the dielectric constants of each component. Considering the influence of the volume fraction of each component on the dielectric properties, the dielectric constant of the composite material can be obtained as:
[0112] ε=v 1 ε 1 +v 2 ε 2 (4)
[0113] Series connection and parallel connection are two extreme cases of composite materials, so the series-parallel hybrid model of composite materials is:
[0114] ε n =v 1 ε 1 n +v 2 ε 2 n (5)
[0115] Where ε is the dielectric constant of the composite material, v 1 and v 2 Represent the volume fractions of matrix and filler, ε 1 and ε 2 Represent the dielectric constants of the matrix and filler respectively; n is a constant, which is -1 for series connection, +1 for parallel connection, and between -1 and +1 for a mixture of series and parallel connection.
[0116] The dielectric constant is a measure of the degree of polarization of a dielectric after being polarized by an electric field, and reflects the ability of an insulating material to store charge. To verify the above theory, a precision impedance analyzer (Agilent 4294A) was used to test the dielectric constant of the PI-CNTs composite film. The test results are as follows: Fig.10 shown. Fig.10 In the figure, a is the dielectric constant measurement curve of PI-CNTs composite film with different CNTs contents; b is Fig.10A partial enlarged view of a.
[0117] Fig.10 The dielectric constant measurement curve of PI-CNTs composite film at different CNTs contents. It can be seen from the figure that the dielectric strength of PI-CNTs composite film gradually increases with the increase of CNTs content. The dielectric strength before doping is 18, but when the CNTs content is 1%, the dielectric constant of PI-CNTs composite film reaches 51. However, when the CNTs content is 1.5%, the increase in dielectric strength is slower. This is because excessive doping of CNTs causes particle agglomeration in the PI matrix, which in turn forms a conductive path, ultimately leading to the generation of leakage current.
[0118] 2. Working Principle of FHTUT (corresponding to the high temperature resistant flexible transducer of the present invention, the same below)
[0119] Any technology related to electromagnetic waves is explained by Maxwell's equations. The theoretical source of the friction nanogenerator also comes from the displacement current derived by Maxwell. In 1861, British physicist Maxwell proposed the displacement current hypothesis based on the basic laws of electromagnetic phenomena derived by his predecessors, called Maxwell-Ampere's law, and summarized a set of partial differential equations that describe the relationship between electric field, magnetic field, charge density and current density. Maxwell's equations include Gauss's theorem, Gauss's magnetic law, Faraday's law and Maxwell-Ampere's law. The specific expressions are as follows:
[0120]
[0121] In the formula, is the Hamiltonian operator, ρ f represents the free charge density, B represents the magnetic field, E represents the electric field, t represents time, H represents the magnetization field, J f represents the free current density, and D represents the electric displacement vector, then:
[0122] D=ε 0 E+P (7
[0123] Where P is the polarization field density caused by the external electric field; ε 0 is the vacuum dielectric constant. The second term on the right side of the Maxwell-Ampere equation is defined as the Maxwell displacement current, let J D represents the displacement current, then:
[0124]
[0125] Under the action of the electric field E, the dielectric material will be polarized, so for isotropic media:
[0126] P=(ε-ε 0)E (9)
[0127] In the formula, ε is the dielectric constant of the dielectric material, so the electric displacement vector can be simplified to D = εE. For the triboelectric effect, polarization will occur even if there is no external electric field in the external environment. Therefore, an additional term P is added to D in the electric displacement vector. s To represent the polarization field density of the static charge on the friction surface, then the electric displacement vector D = εE + P S , then the displacement current becomes:
[0128]
[0129] Formula (10) represents the fundamental source and theoretical basis of the triboelectric transducer. It can be seen that the first term on the right side of the equation is the induced current generated by the changing electric field, and the second term is the current caused by the electrostatic charge polarization field in the triboelectric effect.
[0130] The basic working principle of the friction nanogenerator is to use the coupling of the triboelectric effect and electrostatic induction to achieve the conversion of mechanical energy into electrical energy. Specifically, according to the triboelectric effect, two materials with large differences in electrical polarity will carry equal charges of opposite polarity after contact, and a potential difference will be formed between the two friction materials. When the friction materials move relative to each other, based on the principle of electrostatic induction, the friction charges will be redistributed to balance the potential difference, so a current loop can be formed between the friction materials through an external circuit, thereby converting mechanical vibration energy into electrical energy.
[0131] Here we take the triboelectric transducer in vertical contact-separation mode as an example. Fig.11 (a) shows that the two thicknesses are d 1 and d 2 The friction dielectric material has multiple friction contacts driven by external force. Each time the friction material contacts, a large amount of static charge will be generated on the contact surface, such as Fig.11 (b) As the number of contacts increases, the amount of static charge also increases gradually, and eventually reaches saturation, as shown in Fig.11 (c) as shown. Fig.11 middle, Fig.11 (a) Charge state diagram of the triboelectric transducer showing the vertical contact-separation mode before contact; Fig.11 (b) charge state diagram of the triboelectric transducer showing the vertical contact-separation mode after contact; Fig.11 (c) Charge state diagram of the triboelectric transducer showing multiple contacts in vertical contact-separation mode
[0132] The surface charge density of the material is defined as a time-dependent function σ C (t), the distance between the friction dielectric materials is z, z is a function of time t, and the charge density depends only on the distance z between the dielectrics, d1 and d 2 is the thickness of the dielectric. Based on the principle of electrostatic induction, the static charge caused by friction will establish an electrostatic field when the materials are separated or close to each other, thereby driving electrons to flow between the upper and lower electrodes through the external circuit, resulting in the accumulation of free electrons in the electrodes as σ 1 (z, t), thus realizing the conversion of external mechanical energy into electrical energy. Fig.11 The electric fields in the two dielectrics in (c) are:
[0133] E z1 =σ 1 (z,t) / ε 1 (11)
[0134] Ez 2 =σ 1 (z,t) / ε 2 (12)
[0135] In the formula, ε 1 and ε 2 The dielectric constant of the friction material. The gap in the friction material is air, and its dielectric constant is ε 0 , then the electric field satisfies the following formula:
[0136] E z3 =(σ 1 (z,t)-σ c ) / ε 0 (13)
[0137] Then the relative potential difference between the two electrodes can be expressed as:
[0138] V=σ 1 (z,t)[d 1 / ε 1 +d 2 / ε 2 ]+z[σ 1 (z,t)-σ c ] / ε 0 (14)
[0139] When short circuit occurs, V=0, then:
[0140] σ 1 (z,t)=zσ c / [d 1 ε 0 / ε 1 +d 2 ε 0 / ε 2 +z] (15)
[0141] Finally, from formula (2.10), it can be deduced that the displacement current density inside the material is:
[0142]
[0143] From formula (2.11), we can see that the first term on the right side of the equation indicates that the displacement current density is determined by the movement speed of the friction material separation or contact and the charge density on the surface of the friction material. The second term indicates that the displacement current density is related to the rate of change of the surface charge density. c When saturation is reached, the rate of change of the surface charge density becomes 0, and the displacement current density is:
[0144]
[0145] Assuming that the load of the external circuit is R, according to Ohm's law, its current output equation can be expressed as:
[0146]
[0147] From this formula, the output characteristics of the triboelectric transducer in four working modes can be derived.
[0148] The displacement current theory of Maxwell's equations analyzes the output characteristics of the triboelectric transducer from the perspective of the material's interior, and is the physical core of its current generation. However, it is also necessary to discuss the dynamic output of the triboelectric transducer in the presence of an external circuit. The working principle of the triboelectric transducer is the coupling of the contact electrification effect and electrostatic induction. The most basic electronic component based on the electrostatic induction phenomenon is the capacitor, so the triboelectric transducer has an inherent capacitance property. Therefore, the triboelectric transducer is approximated as a capacitor model, and the capacitor equation is used to represent the external output performance of the displacement current.
[0149] For any triboelectric transducer, external force causes the friction materials to contact and separate with each other, and equal but opposite induced charges will be generated on the surface of the materials. When the distance between the friction materials changes, the charges flow between the electrodes on the back of the friction materials through the external circuit, and a voltage is formed between the two electrodes. Assuming that the amount of charge transferred between the electrodes is -Q and +Q respectively, and the capacitance between the two plates is C(x), the triboelectric transducer can be equivalent to a capacitor model, then the potential difference formed between the two electrode plates by the transferred charges is Q / C(x). Assuming that the output voltage generated by the friction charge is V oc (x), is a function of the relative distance x of the friction material. Then, according to the principle of potential superposition, the total potential difference is equal to the voltage V generated by the friction charge. oc The sum of the voltage Q / C(x) and the transferred charge can be expressed as:
[0150]
[0151] Equation (19) can represent the governing equation for any triboelectric transducer and explains the inherent capacitive properties of triboelectric devices. The separation of triboelectric charges creates a potential difference between the electrodes, which forces electrons to flow in the external circuit. Therefore, the potential distribution also depends on the amount of charge that has been transferred. Under short-circuit conditions, the transferred charge Q sc The potential difference caused by the friction charge will be completely offset, and then:
[0152]
[0153] Therefore Q sc , C and V oc (x) The basic relationship between the three is:
[0154] Q sc =C(x)V oc (x) (21)
[0155] From the above analysis, it can be seen that formula (21) is the VQx equation of the triboelectric transducer under short-circuit conditions.
[0156] Under the coupling effect of triboelectric charging and electrostatic force, FHTUT has two functions: ultrasonic emission and reception. For ultrasonic emission, the electrostatic force between the electrodes can drive the FHTUT to undergo mechanical deformation and cause the particles around the medium to vibrate, thereby emitting ultrasonic waves outward to achieve the conversion of electrical energy into acoustic energy. For ultrasonic reception, the external ultrasonic sound field can drive the FHTUT to undergo mechanical deformation and cause its internal friction layer to generate friction charges through contact separation, thereby generating electrical signals through an external circuit to achieve the conversion of acoustic energy into electrical energy. In order to obtain the vibration equation of the rectangular PI film, it is assumed that the uniformly tensioned PI flexible film of equal thickness is in the xy plane with uniform tension. The length and width of the PI flexible film are m and n respectively, and the displacement of any point on the film in the vertical direction (z-axis direction) after leaving the initial position is η. Take a rectangular surface element dxdy on the PI film, and the coordinates of the lower left corner of the surface element are (x, y), such as Fig.12 As shown. Ignoring the stiffness of the film, the rectangular surface element can be regarded as composed of countless chord elements, with a length of dx and a width of one unit. The tension on the rectangular surface element can be decomposed into each chord element, and the direction of the tension on the chord element is consistent with the tangent direction of the chord element. Let the angle between the tension T and the coordinate axis x be α, then the component of the tension in the y-axis direction is T sinα. When the vibration amplitude is relatively small, sinα≈tanα.
[0157] Then the tension in the vertical direction of the dy edge is:
[0158]
[0159] The tension in the vertical direction of the dx edge is:
[0160]
[0161] Therefore, the tension force of the surface element in the vertical direction of the dy edge is:
[0162]
[0163] Similarly, the tension force of the surface element in the vertical direction of the dx edge is:
[0164]
[0165] So the total vertical tension of the surface element is F z for:
[0166]
[0167] Considering that the membrane of the triboelectric hydrophone is forced to vibrate under the action of sound pressure, it is assumed that the vertical uniform sound pressure on the membrane surface is:
[0168] P=P a e jωt (27)
[0169] Where P a is the amplitude of the sound pressure, in N / m 2 , ω is the circular frequency of the sound pressure.
[0170] Then, the external sound pressure force received on the panel is:
[0171] F F =Pdxdy (28)
[0172] Since the air cavity in the triboelectric hydroacoustic transducer unit will produce a reaction force on the PTFE film, assuming that the surface resistance coefficient of the air cavity is R, the reaction force generated is:
[0173]
[0174] Finally, the total sound pressure external force on the panel can be obtained as follows:
[0175]
[0176] Assuming that σ is the surface density of the film, that is, the mass of the film per unit area, then σdxdy is the mass of the surface element, and the equation of motion of the surface element can be calculated according to Newton's second law:
[0177]
[0178] Let c2 =T / σ, then formula (31) can be simplified to obtain the vibration equation of the rectangular PTFE film:
[0179]
[0180] To solve the expression for the vertical displacement η, first, let f(t) = P a e jωt / c 2 σ, formula (32) can be converted into:
[0181]
[0182] Then, the impulse theorem is used to homogenize the problem. τ represents the impulse start time. Then formula (33) can be changed to:
[0183]
[0184] Formula (34) has a second-type boundary condition
[0185] Then, we use the separation of variables method on formula (34) and let γ(x,y,t)=X(x)Y(y)T(t). Then the original equation becomes:
[0186]
[0187] Dividing both sides of the above equation by X(x)Y(y)T(t) yields:
[0188]
[0189] In the above equation, the left side is only related to x and y, and the right side is only related to t, and it is true for any x, y, and t, so both sides of the equation are always equal to a constant that is independent of x, y, and t. Let the constant be -λ, then the above equation can be split into two independent equations:
[0190]
[0191]
[0192] Formula (37) needs to be solved again using the separation of variables method, and the second separation constant -μ is introduced to obtain:
[0193]
[0194] It can be seen that formula (39) transforms the surface element vibration problem into a one-dimensional string vibration problem. Let ν = λ-μ, we can get:
[0195]
[0196]
[0197] The eigenvalues and eigensolutions of X(x) and Y(y) can be obtained as:
[0198]
[0199] In the formula, A p is a constant coefficient and can be calculated according to the boundary conditions X(0)=0 and X(m)=0 of formula (41), where m is the length of the PTFE film on the x-axis.
[0200]
[0201] In the formula, B q is a constant coefficient, which is calculated according to the boundary conditions Y(0)=0 and Y(n)=0 of formula (42), where n is the length of the PTFE film on the y-axis.
[0202] Therefore, we can get:
[0203]
[0204] Next, solve formula (42) and the original equation can be transformed into:
[0205]
[0206] The characteristic equation roots of formula (45) can be solved as:
[0207]
[0208] Since it is impossible to measure the specific values of constants such as R and T, R 2 -4λT 2 There are three cases: greater than zero, less than zero, and equal to zero. The general solution of the characteristic equation is different in different cases, but the solution method is similar, so here we only discuss the case when R 2 -4λT 2 When is greater than zero, the solution of the formula can be expressed as:
[0209]
[0210] In the formula, C pq and D pq is a constant coefficient and can be solved by the initial condition of the vertical displacement of the membrane.
[0211] By integrating formula (47), the vertical displacement η of the rectangular PTFE film can be obtained as:
[0212]
[0213] Its initial conditions are:
[0214]
[0215]
[0216] It can be seen that the vertical displacement η(x,y,t) is a related function of position and time.
[0217] Furthermore, the finite element analysis software COMSOL was used to couple the driving effects of the external electric field and acoustic field on the FHTUT. In the simulation model, the FHTUT transmitter and the FHTUT receiver are located on the upper and lower surfaces of the acrylic block, respectively. The dimensions of the two transducers are 10 mm × 10 mm, the thickness of the single-layer film is 50 μm, and the potential between the upper and lower electrodes of the FHTUT transmitter is 10 V and 0 V, respectively. Fig.13 The coupled simulation results of FHTUT in transmit mode and receive mode are shown; Fig.13 In the figure, a is the overall view, b is the XOY plane view, where the signal frequency is 1 MHz.
[0218] from Fig.13 It can be seen that under the driving action of the external electric field, the FHTUT transmitter can emit an ultrasonic sound field into the medium, and the sound field propagates outward in a hemispherical shape with the center of the FHTUT as the center. Under the driving action of the ultrasonic sound field, the FHTUT receiver undergoes mechanical deformation. In summary, the working principle of the transducer also involves the coupling of multiple physical fields, and its transmission mode and receiving mode need to be analyzed from the aspects of acoustics, electricity and mechanics.
[0219] How Transmit Mode Works
[0220] In the transmitting mode, due to the potential difference between the upper and lower electrodes of the FHTUT, there is an electrostatic force between the two electrodes. According to the theoretical analysis of the transducer lumped parameter system model, the electrostatic force will further drive the FHTUT to undergo mechanical deformation, and the deformation state of the transducer is positively correlated with the magnitude of the electrostatic force. Fig.14 The steady-state potential distribution of FHTUT at different initial voltages is shown. Fig.14 In the figure, a means the voltages of the upper and lower electrodes are both 0V; b means the voltages of the upper and lower electrodes are 10V and 0V respectively. Fig.14 It can be seen that when the initial voltages of the upper and lower electrodes are both 0V, there is no potential difference between the two electrodes in the transducer; when the initial voltages of the upper and lower electrodes are 10V and 0V respectively, there is a potential difference between the two electrodes of the transducer.
[0221] On this basis, when the external electric field changes, the electrostatic force between the two electrodes of the transducer also changes, which in turn causes the deformation state of the transducer to change. Fig.15 The deformation state of FHTUT under the action of electric fields of different frequencies is shown. Fig.15 It can be seen that as the frequency increases, the wavelength of the sound wave gradually decreases, and the number of peaks and troughs on the transducer surface increases. Furthermore, the change in the deformation state of the FHTUT will cause the vibration of the particles in the surrounding medium, thereby emitting ultrasonic waves outward and realizing the conversion of electrical energy into acoustic energy.
[0222] 3. Working principle of FHTUT receiving mode
[0223] Under the action of the external electric field, the FHTUT as a transmitter radiates ultrasonic waves outward. The ultrasonic waves propagate through the medium to the surface of the FHTUT as a receiver. Similarly, according to the theory of forced vibration of the membrane, the sound wave will generate a pressure difference between the upper and lower surfaces of the FHTUT receiver, thereby causing the FHTUT as a receiver to undergo mechanical deformation. Fig.16 Indicates the deformation state of FHTUT under the action of ultrasonic sound fields of different frequencies. Fig.16 It can be seen that as the frequency increases, the wavelength of the sound wave gradually decreases, while the number of peaks and troughs on the transducer surface gradually increases. The above results show that the external sound field has a certain driving effect on the deformation of the transducer.
[0224] Furthermore, the deformation of FHTUT will cause contact separation of its internal microstructure. Based on the triboelectric effect, the contact between different materials will generate friction charges on their contact surfaces. Compared with copper metal, PI has stronger electronegativity, that is, it has a stronger ability to gain electrons. When PI contacts copper, the surface of PI is negatively charged due to gaining electrons, while the surface of copper is positively charged due to losing electrons.
[0225] In addition, based on the principle of electrostatic induction, the periodically changing sound pressure causes the contact state between the friction layers inside the FHTUT to change, thereby causing the induced charge to be transferred from the external circuit, such as Fig.17 Similarly, from the theory of the two-electrode vertical contact separation mode, it can be known that the open circuit voltage V between the two electrodes of the transducer OC It can be expressed as:
[0226]
[0227] Where σ is the surface charge density, x is the air gap distance, and ε 0 is the dielectric constant of air. From the above formula, we can know that the open circuit voltage V OCIt is positively correlated with the separation distance x(t) and the surface charge density σ. In the initial state, based on the principle of charge conservation, the PI and copper surfaces carry equal amounts of negative and positive charges, respectively. Under the action of external pressure, the transducer deforms, and according to the principle of electrostatic induction, the electrons on the surface of the upper electrode are transferred to the lower electrode through the external circuit. As the deformation intensifies, the electrons on the surface of the upper electrode continue to transfer to the lower electrode.
[0228] In order to more intuitively understand the potential change during the charge transfer process, the finite element analysis software COMSOL is used to simulate and analyze the potential distribution of the transducer under different deformation states. Fig.17 As shown, Fig.17 The a row in the middle is a schematic diagram of charge transfer. Fig.17 The middle row b shows the simulation results of the electric potential distribution of the high temperature resistant flexible transducer in three deformation states. Fig.17 It can be seen that as the deformation state intensifies, the charge is transferred through the external circuit and the potential difference inside the transducer gradually decreases. This result is consistent with the above charge transfer theory.
[0229] CNTs form a nano-protrusion structure on the surface of the micron-scale structure, and then form a micro-nano dual-level structure on the surface of the friction layer. Under the action of external force, the micro-nano dual-level structure undergoes extrusion contact, which can be assumed to be the contact between two elastic hemispheres. Similarly, according to Hertz theory, the relationship between the contact area S and the external force F satisfies:
[0230]
[0231]
[0232] In the formula, is the angle between the external force F and the vertical direction, R 1 and R 2 are the radius of the hemisphere of the micro / nano structure, μ 1 and E 1 are the Poisson's ratio and elastic modulus of the lower hemisphere, μ 2 and E 2 are the Poisson's ratio and elastic modulus of the upper hemisphere, respectively. It can be seen from the above formula that under the action of external force F, the upper and lower layers of the structure gradually approach each other, and the interlocking structure will have extrusion contact, and the contact area A is positively correlated with the external force F.
[0233] In addition, compared with conventional planar film structures and single-stage micron interlocking structures, PI-CNTs composite films with micro-nano dual-stage interlocking structures are more sensitive to external forces. In order to analyze the response capabilities of different structures to weak pressure (including external sound pressure and internal electrostatic force), the finite element analysis software COMSOL was used to compare and analyze the deformation states of planar structures, single-stage interlocking microstructures, and micro-nano dual-stage interlocking structures under external forces. The simulation results are shown in Figure 2. Fig.18 As shown, Fig.18 In the figure, row a is a planar structure; row b is a single-stage interlocking structure; row c is a micro-nano double-stage interlocking structure; and row d is the stress distribution simulation results of the three structures. Fig.18 In the figure, Flat structure is a planar structure, Interlocking structure is a single-stage interlocking structure, Interlocking structure (no air) is a micro-nano double-stage interlocking structure, Pressure is pressure, and Normalized stress is dimensionless pressure.
[0234] from Fig.18 It can be seen that compared with the other two structures, the stress of the micro-nano two-stage interlocking structure is more concentrated and the deformation displacement is larger. This result further shows that the introduction of the micro-nano two-stage interlocking structure plays an important role in improving the sensitivity of the transducer.
[0235] 4. FHTUT performance calibration method (the content of CNTs in FHTUT is 1%)
[0236] Laser vibrometer can perform non-contact high-precision measurement of the surface of an object through laser and photoelectric detection technology. Therefore, a high-precision laser vibrometer is selected to accurately and quantitatively test the transmission and receiving performance of FHTUT. However, due to the limitation of the operating frequency range of the laser vibrometer itself, 0.2-1.5MHz is selected as the actual sweep frequency range.
[0237] For the emission performance of FHTUT, the vibration velocity at the center of the FHTUT surface can be directly obtained using a laser vibrometer. Fig.19 As shown, Fig.19 a in the figure is the vibration velocity curve at the center of the FHTUT surface at different frequencies; Fig.19 Figure b shows the vibration velocity curve of the acrylic block surface at different frequencies and the sensitivity curve of the FHTUT receiver. Fig.19 It can be seen from a that the vibration velocity curve of FHTUT can be roughly divided into two sections: in the frequency range of 0.2-1.2MHz, the vibration velocity increases with the increase of frequency; in the frequency range of 1.2-1.5MHz, the vibration velocity decreases with the increase of frequency, and the peak-to-peak value of the vibration velocity can reach 14.5mm / s.
[0238] For the receiving performance of FHTUT, its receiving sensitivity The formula Calculated. Among them, the voltage amplitude of the FHTUT receiving signal is U, and the vibration speed of the acrylic block surface is v. In order to facilitate comparison with other transducers, the unit of transducer sensitivity is further converted to dB using the conversion principle of 0dB=1V / m / s.
[0239] from Fig.19 It can be seen in Figure b that the vibration velocity curve on the surface of the acrylic block can be roughly divided into two sections. In the frequency range of 0.2-1.0MHz, the vibration velocity increases with the increase of frequency; in the frequency range of 1.0-1.5MHz, the vibration velocity decreases with the increase of frequency. The receiving sensitivity curve of FHTUT can also be roughly divided into two sections. In the frequency range of 0.2-0.9MHz, the receiving sensitivity first increases and then decreases with the increase of frequency; in the frequency range of 0.9-1.5MHz, the receiving sensitivity gradually increases with the increase of frequency, but the increase rate is slow. The above test results show that FHTUT has good transmitting and receiving performance, and its receiving sensitivity can reach up to 33.5dB, which is conducive to subsequent high-precision ultrasonic detection application tests.
[0240] In high temperature environments, conventional ultrasonic transducers are prone to malfunction and failure, which results in inaccurate measurement data and affects the normal operation of the entire system. Transducers with good temperature resistance can work stably in high temperature environments, thereby improving the reliability of the system. In order to analyze the temperature resistance of FHTUT, the high temperature performance test platform was used to test FHTUT with different CNTs contents. The test results are shown in Figure 2. Fig. 20 As shown, Fig. 20 Figure a shows the output signal waveform of FHTUT in the self-transmitting and self-receiving mode, where the excitation signal frequency is 1MHz and the number of cycles is 4. As can be seen from the figure, the output signal mainly contains excitation signal interference, primary reflection echo and secondary boundary echo. Among them, the amplitude of the primary boundary echo can be used to characterize the output performance of the transducer, and the flight time between the primary boundary echo and the excitation echo interference signal can be used to measure the specific thickness of the test block. Fig. 20 Figure b is the amplitude curve of the primary boundary echo signal of FHTUT with different CNTs contents at different temperatures. Fig. 20It can be seen from Figure b that the output voltage of FHTUT with different CNT contents decreases with the continuous increase of temperature. At the same time, when the CNTs content is lower than 1%, with the continuous increase of CNTs, the output voltage and temperature resistance of FHTUT are significantly enhanced, and the temperature resistance value under -3dB attenuation can reach 210°C. However, when the CNTs nanopowder accounts for 1.5% of the total mass of PI-CNTs, the temperature resistance of FHTUT decays. This is because when the CNTs content is 1.5%, CNTs agglomeration occurs inside the composite film, which limits the further enhancement of its temperature resistance. The test results show that the introduction of a certain amount of CNTs can enhance the temperature resistance of FHTUT. Therefore, FHTUT with a CNTs content of 1% was selected for subsequent testing and application.
[0241] 5. FHTUT Ultrasonic High Temperature Thickness Measurement
[0242] In order to verify that the optimized FHTUT has good temperature resistance, the FHTUT was compared with a commercial ultrasonic thickness gauge. The test blocks were steel blocks with different surface temperatures and thicknesses, such as Fig.21 As shown, Fig.21 a in the middle is the actual picture of FHTUT thickness measurement on site; Fig.21 b in the middle is the actual picture of the thickness gauge measuring on site; Fig.21 Figure c in the middle is a comparison diagram of thickness measurement results;
[0243] Among them, the surface temperature of the steel block is 25℃ and 200℃ respectively, and the actual thickness of the test block is 29.47mm, 50.04mm and 70.06mm respectively. Further, the thickness of the test block can be calculated by the formula
[0244] It is calculated by h=v*T / 2, where v is the speed of sound in the medium, which can be calibrated by a test block of the same material, and T is the time difference between the reflected echo and the transmitted wave.
[0245] Fig. 20 Figure c shows the calculated results of the steel block thickness obtained using a commercial ultrasonic thickness gauge and FHTUT. At the same time, the same test block was measured 5 times and the average value was taken to reduce the system error. When the surface temperature of the steel block is 25°C, both the commercial ultrasonic thickness gauge and FHTUT can accurately measure the thickness of the test block. For a steel block with an actual thickness of 29.47mm, the relative errors of the two calculation results are comparable, at 0.29% and 0.24%, respectively. When the surface temperature of the steel block is higher than 200°C, the transducer can still measure the thickness.
[0246] However, due to the thermal stability of the material inside the probe, the ultrasonic thickness gauge cannot perform thickness measurement. The specific measurement results are shown in Table 1 (the test block thickness measurement results obtained by commercial ultrasonic thickness gauge and FHTUT at different temperatures).
[0247] Table 1
[0248]
[0249]
[0250] 6. FHTUT is used for quantitative detection of high-temperature pipeline defects (the content of CNTs in FHTUT is 1%)
[0251] In industrial production, it is very necessary to conduct quantitative detection and analysis of industrial structures. It can quantitatively characterize the size and location of various defects in the structure, help inspectors determine whether the structure is safe and reliable, and then decide whether the structure needs to be repaired, replaced or strengthened. At the same time, quantitative defect detection can provide basic data for later detection for health monitoring and evaluation. In actual ultrasonic reflection detection, the defect size is related to the flight time and amplitude of the ultrasonic echo signal. Therefore, quantitative defect detection can be achieved by calculating the time delay and signal amplitude of the defect echo signal. FHTUT has good ultrasonic transmission and reception performance, and is flexible and high temperature resistant. It can be used for quantitative detection of internal defects in high-temperature industrial equipment.
[0252] The overall design scheme of the high-temperature pipeline defect quantitative detection test system is as follows: Fig. 22 shown. Fig. 22 In the figure, DC power is the DC power supply, Computer is the computer, Logic Iput Controller is the logic input controller, Ultrasound Transceiver is the ultrasonic transceiver, Data Acquisition is the data acquisition, Pipe is the pipe to be tested, Heatingplate is the micro heating plate, Power is the power supply of the micro heating plate, Echo is the echo, and Defect is the defect;
[0253] First, an artificial groove is machined on the inner wall of the vertically cut pipe using a precision mechanical bench drill to simulate actual corrosion defects. To achieve quantitative detection of defects, the diameter of the groove needs to be kept constant and the depth of the groove needs to be continuously deepened. Then, the FHTUT is installed on the outer wall of the high-temperature pipe through a high-temperature coupling agent, and the FHTUT and the artificial groove are ensured to be in the same vertical direction. Finally, a micro heating plate is placed at the position of the groove. Under the power supply of a DC power supply, the heating plate can heat the outer wall of the pipe to the required temperature to simulate the high-temperature surface of the pipe.
[0254] The specific test steps are as follows: ① Use the logic input controller to generate a low-voltage high-frequency pulse control signal, and transmit the control signal to the transducer after voltage amplification through the ultrasonic transceiver, so that the transducer can generate the corresponding ultrasonic wave as a transmitter. ② Use the FHTUT as a receiver to receive the echo signal, and use the T / R module in the ultrasonic transceiver to limit the echo signal to avoid damage to the data acquisition device due to high voltage. ③ The limited signal is transmitted to the LabVIEW software program through the data acquisition device for real-time display and recording. ④ Use MATLAB software to filter the signal and draw the envelope, and calculate the time delay between the direct wave and the defect reflection echo, so as to realize the quantitative detection of defects. During the test, the high-voltage power supply is used to power each module in the ultrasonic transceiver.
[0255] In order to test the high-temperature pipeline defect quantitative detection test system, a 45# vertically cut steel pipe with an outer diameter of 204mm and a wall thickness of 38mm was selected for the test. Before the test, it is necessary to process an artificial circular groove with a diameter of 10mm on the inner wall of the pipe and heat the pipe surface to about 200℃. Then, the FHTUT is installed on the outer surface of the pipe to transmit and receive ultrasonic signals, such as Fig.23 As shown, Fig.23 Middle a shows the FHTUT installed on the pipeline; Fig.23 Figure b shows defects on the inner wall of the pipe.
[0256] Under the stimulation of high-voltage electric pulses, FHTUT will emit ultrasonic waves into the high-temperature pipeline. When the ultrasonic waves encounter the discontinuous interface, they will generate reflected echoes and then be received by FHTUT again. In order to analyze the interaction between ultrasonic waves and defects, the finite element analysis software COMSOL is used to simulate the ultrasonic waves generated by FHTUT in the defective pipeline models of different sizes. The simulation results are shown in Figure 2. Fig.24 shown. Fig.24 middle, Fig.24 Figure a shows the simulated propagation cloud diagram of ultrasonic waves in the pipe wall thickness; Fig.24 Middle b shows the ultrasonic signal waveform at different groove depths; Fig.24 Middle c shows a local enlarged view of the signal waveform; Fig.24 Figure d shows the flight time and amplitude curves of the reflected echo at different groove depths.
[0257] from Fig.24 It can be seen from a that the ultrasonic signal includes longitudinal waves and transverse waves, and the longitudinal wave has a faster speed. In addition, as the defect depth increases, the defect reflection echo is generated earlier.
[0258] Since the displacement direction of FHTUT under the action of external force is mainly perpendicular to the plane in which it is located, the shear wave component is effectively suppressed and filtered out. Furthermore, only longitudinal wave signals exist in the received waveform of FHTUT, which has the characteristics of single mode. Fig.24 It can be seen from Figure 24b and Figure 24c that when there is no groove, the signal waveform only has the transmission signal and the echo signal of the inner wall of the pipe; when there is a groove, the defect reflection echo signal appears in the signal waveform. In order to quantitatively compare the waveform differences of the defect reflection echo signal under different groove depths, the flight time and amplitude of the defect reflection signal are statistically analyzed, as shown in Figure 24c. Fig.24 As shown in d. Fig.24 It can be seen from figure d that as the groove depth increases, the defect reflection echo appears earlier and the signal amplitude gradually increases. This result is consistent with the above theoretical analysis.
[0259] Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent substitutions for some of the technical features therein; and these modifications or substitutions do not make the essence of the corresponding technical solutions deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A high temperature resistant flexible transducer, characterized in that: It comprises a PI-CNTs stacked film layer (10) and a packaging layer (20) bonded to the upper and lower surfaces of the PI-CNTs stacked film layer (10); The PI-CNTs stacked film layer (10) is formed by interlocking a positive electrode PI-CNTs composite film and a negative electrode PI-CNTs composite film. The positive electrode PI-CNTs composite film and the negative electrode PI-CNTs composite film are both composed of a PI-CNTs composite film (11) with a micro-nano dual-level structure and a copper layer (12) attached to the surface of the PI-CNTs composite film. PI is the abbreviation of polyimide, and CNTs is the abbreviation of carbon nanotubes.
2. A high temperature resistant flexible transducer according to claim 1, characterized in that: The packaging layer (20) is composed of a single-sided adhesive film made of a silicone-based high-temperature fireproof material.
3. A high temperature resistant flexible transducer according to claim 2, characterized in that: The specific preparation process of the single-sided adhesive film is as follows: The silicone-based colloid is dropped onto a glass substrate and coated into a film using a coater; Curing at room temperature for 2-3 hours to obtain a single-layer sealing film; The high-temperature sealing colloid is dropped again on the surface of the solidified single-layer high-temperature sealing film, and is spread evenly using a coater to obtain a single-sided adhesive film.
4. A high temperature resistant flexible transducer according to claim 3, characterized in that: The thickness of the single-sided adhesive film is 40-50 μm.
5. The high temperature resistant flexible transducer according to claim 1, characterized in that: The thickness of the PI-CNTs composite film (11) is 50-70 μm.
6. The high temperature resistant flexible transducer according to claim 1, characterized in that: The copper layer (12) has a thickness of 300-350 nm.
7. The high temperature resistant flexible transducer according to claim 1, characterized in that: The PI-CNTs stacked thin film layer (10) comprises the following steps: The uniformly dispersed PI-CNTs mixed solution is evenly spin-coated on the semicircular pit template, and then heated and cured, and peeled off to obtain a PI-CNTs composite film (11) with a micro-nano dual-level structure on the surface; Depositing copper on the front side of a PI-CNTs composite film (11) and the back side of another PI-CNTs composite film (11) to obtain a positive electrode PI-CNTs composite film and a negative electrode PI-CNTs composite film; The positive electrode PI-CNTs composite film and the negative electrode PI-CNTs composite film are stacked in a manner that the film surfaces with copper attached are facing each other, thereby obtaining a PI-CNTs stacked film layer (10).
8. The high temperature resistant flexible transducer according to claim 7, characterized in that: The PI-CNTs mixed solution is made of CNTs nano powder and PI solution, and the CNTs nano powder accounts for 0-1.5% of the mass of the PI-CNTs composite film (11), excluding zero.
9. The high temperature resistant flexible transducer according to claim 7, characterized in that: The spin coating speed is 800-900 r / s.
10. The high temperature resistant flexible transducer according to claim 7, characterized in that: The conditions for heating and curing are: heating rate of 60-70°C / h, keeping warm at 80-90°C for 1-1.5 hours, keeping warm at 140-145°C for 1-2 hours, and keeping warm at 260-270°C for 1-2 hours.
11. A high temperature resistant flexible transducer according to any one of claims 7 to 10, characterized in that: The deposition method is magnetron sputtering.
12. A method for preparing a high temperature resistant flexible transducer, characterized in that: A high temperature resistant flexible transducer according to any one of claims 1 to 11 is manufactured, comprising: The uniformly dispersed PI-CNTs mixed solution is evenly spin-coated on the semicircular pit template, and then heated and cured, and peeled off to obtain a PI-CNTs composite film (11) with a micro-nano dual-level structure on the surface; Depositing copper on the front side of a PI-CNTs composite film (11) and the back side of another PI-CNTs composite film (11) to obtain a positive electrode PI-CNTs composite film and a negative electrode PI-CNTs composite film; The positive electrode PI-CNTs composite film and the negative electrode PI-CNTs composite film are stacked in a manner that the film surfaces with copper attached face each other, thereby obtaining a PI-CNTs stacked film layer (10); A single-sided adhesive film is stacked on the upper and lower surfaces of the PI-CNTs stacked film layer (10), and a stainless steel roller is used to roll the PI-CNTs stacked film layer (10) from one side to the other side to form a packaging layer (20), thereby obtaining a flexible transducer.
13. An application of a high temperature resistant flexible transducer, characterized in that: Application of the high temperature resistant flexible transducer described in any one of claims 1 to 11 for thickness measurement at 0-200°C and quantitative detection of pipeline defects.